Sb2O3@Sb nanoparticles impregnated in N-doped carbon microcages for ultralong life and high-rate sodium ion batteries. Issue 20 (12th May 2021) - Xu, Anding; Huang, Chuyun; Li, Guilan; Zou, Kaixiang; Sun, Hao; Fu, Lili; Ju, Jiahao; Song, Yang; Wu, Songping; Xu, Zhiguang; Yan, Yurong
Abstract : Herein, Sb2 O3 @Sb nanoparticles impregnated in N-doped carbon microcages with multi-scale structural nature, including hierarchical heterogeneous structure and heteroatom doping, could significantly enhance sodium/potassium storage capabilities. Abstract : Antimony-based materials have been considered as highly competitive anodes for sodium-ion batteries (SIBs) because of their high theoretical capacity. However, the poor rate capability and fast capacity fading, originating from sluggish kinetics and volume expansion, greatly restrict their practical application. To address the above issues, an effective spraying method and one-step partial reduction process were utilized to synthesize Sb2 O3 @Sb nanoparticle impregnated in N-doped carbon microcages (Sb2 O3 @Sb@NC) offering extraordinary sodium storage capabilities and delivering an ultra-high rate performance of 175.1 mA h g −1 at 20 A g −1 and a superior capacity retention of 245.2 mA h g −1 after 10 000 cycles under 10 A g −1 for SIBs. Such unprecedented electrochemical properties of the Sb2 O3 @Sb@NC electrode can be ascribed to the comprehensive characteristics derived from multi-scale structural engineering: the fast electrochemical kinetics and tight packing of Sb2 O3 @Sb nanoparticles with carbon sheets, the strong Na + adsorption ability of Sb2 O3 @Sb@NC enhanced by the synergistic effect of heterostructures and N-doping, the structural integrity strengthened by a robust interface bond of Sb–O–C, and the improved pseudocapacitive contribution. These distinct features enable the Sb2 O3 @Sb@NC anode to be a potential candidate for large-scale sodium ion storage.